Human resource management practices for promoting sustainability - Atiku, Sulaiman Olusegun, 1980-; Fapohunda, Tinuke, 1970- (Business Science Reference, 2020)
"This book explores human resource management practices for promoting sustainability in the fourth industrial revolution"--